A note on long-distance matches of bottlenose dolphins (Tursiops truncatus) around the Irish coast using photo-identification - O'Brien, Joanne M.; Berrow , Simon D.; Ryan, Conor; McGrath , David; O'Connor , Ian; Pesante , Giovanna; Burrows , Gary; Massett , Nick; Klotzer , Vanessa; Whooley , Padraig (J. Cetacean Res. Manage., 2023)
Images of 120 individual bottlenose dolphins from around the Irish coast were obtained from three photo-identification catalogues. Twenty three individuals were subsequently re-sighted, which is a re-sighting rate of 19%. The distance between re-sightings ranged from 130 to 650km and the duration from 26 to 760 days. Images were also compared to a catalogue of resident dolphins from the Shannon Estuary candidate Special Area of Conservation and from Wales but no matches were found. This short study provides strong evidence that bottlenose dolphins in Irish coastal waters are regularly undertaking large movements around the entire Irish coast and must be considered highly mobile and transient. These results have important implications for the conservation and management of this species.